Chapitre II. Le consentement à l’arbitrage, manifestation d’une volonté contenue - Diallo, Ousmane (Le consentement des parties à l'arbitrage international, 2010)

Chapter 42, Dissenting Opinions by Party-Appointed Arbitrators in Investment Arbitration - van den Berg, Albert Jan (Looking to the future: essays in international law in honor of W. Michael Reisman, 2010)
Dissenting opinions appear to have become an accepted practice in international arbitration. Th e current debate concentrates on their procedure, form, and content. Alan Redfern noted that “[a]t present, a generally relaxed attitude towards dissenting opinions seems to be taken not only by the arbitral institutions, but also by the arbitrators themselves … .” In this contribution, I would like to explore the cautionary note with which Redfern concluded his seminal article, namely, that the “[t]ime has perhaps come to inquire whether the present leniency towards dissenting opinions … has gone too far.” I propose to do so with respect to investment arbitrations because ade available publicly, particularly party-appointed arbitrators’ dissenting opinions.
Keywords: Arbitrage; Arbitration; Arbitrator; Dissenting opinion; Investment arbitration; Opinion dissidente